eCM 2018
DOI: 10.22203/ecm.v035a24
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of auricular chondrocytes in poly(ethylene glycol)/poly(ε-caprolactone) hydrogel for tracheal cartilage tissue engineering in a rabbit model

Abstract: Tissue engineering has the potential to overcome the limitations of tracheal reconstruction. To tissue-engineer a tracheal cartilage, auricular chondrocytes were encapsulated in a photocurable poly(ethylene glycol)/poly(ε-caprolactone) (PEG/PCL) hydrogel. Chondrogenic genes, including Sox9, Acan and Col2a1, were up-regulated in auricular chondrocytes after 2 weeks of in vitro cultivation in the PEG/PCL hydrogel. Co-cultivation of 70 % auricular chondrocytes and 30 % bone marrow mesenchymal stem cells (BMSCs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate laryngeal tissue engineering 85‐87,91,92,94,96,97,198‐306 …”
Section: Discussionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate laryngeal tissue engineering 85‐87,91,92,94,96,97,198‐306 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several studies have demonstrated that 3D culture of chondrocytes can promote cellular proliferation without changing phenotypes. For example, rabbit articular chondrocytes cultured on poly(ethylene glycol)/poly(ε-caprolactone) (PEG/PCL) hydrogel led to the up-regulated expression of chondrogenic genes such as Sox-9, aggrecan, and Col II in 2 weeks, and increased proteoglycans and Col II accumulation after 4 weeks ( Chang et al, 2018 ). Therefore, in order to retain the phenotype of implanted chondrocytes, a favorable strategy is to incubate them in a 3D culture environment before seeding.…”
Section: Cartilage Tissue Engineering For Gp Injuriesmentioning
confidence: 99%
“…Chondrocytes, encapsulated in the ethylene glycol diacrylate/chondroitin sulfate‐methacrylate hydrogel, can greatly proliferate, retaining their classic rounded morphology . The microenvironments of poly(ethylene glycol)/poly(ε‐caprolactone) hydrogel favor the proliferation of the loaded chondrocytes, meanwhile, who retain chondrogenic potential …”
Section: Therapeutic Cells and Growth Factorsmentioning
confidence: 99%